Model-based optimization of xylooligosaccharides production by hydrothermal pretreatment of Eucalyptus by-product - Neto, Flávia Sanchez Penalva P. [UNESP]; Roldán, Ismael Ulises Miranda [UNESP]; Galán, Julián Paul Martínez; Monti, Rubens [UNESP]; de Oliveira, Samuel Conceição [UNESP]; Masarin, Fernando [UNESP] (Elsevier, 2020)
Eucalyptus wood is the main source of fiber for the production of paper and cellulose in South America. One of the by-products of the pulp industry is sawdust generated during wood chip production; sawdust from Eucalyptus is denominated as Eucalyptus by-product (EB). Xylooligosaccharides (XOS) are oligomers mainly comprising xylose units, which have beneficial effects on health. In this study, was report the optimization of XOS production through the hydrothermal pretreatment (HP) of EB. A central composite experimental design comprising a 23-factorial design with six axial points and four replicates at the central point was employed to optimize the HP conditions for maximum XOS production using response surface method; these conditions were as follows: temperature of 161 °C, reaction time of 65 min, and consistency of 10 %. The hemicellulosic hydrolysate showed potential for the production of XOS, containing 60 milligrams of XOS per gram of EB.
Keywords: Autohydrolysis; Eucalyptus; Experimental design; Response surface; Xylooligosaccharides (XOS)